Does a Leu 512 Arg thyrotropin receptor mutation cause an autonomously functioning papillary carcinoma? - GÖZÜ, HÜLYA; GÜLLÜOĞLU, MAHMUT BAHADIR; ÖNEŞ, TUNÇ (MARY ANN LIEBERT INC, 2004)
In the last decade, studies were first done to determine the frequency of G(s)alpha and later thyrotropin receptor (TSHR) mutations in benign autonomously functioning thyroid nodules (AFTN). Different frequencies ranging from 0% to 38% for G(S)p mutations and from 20% to 86% for TSHR mutations were found. There were only some limited case reports related to TSHR genetic alterations in malignant AFTN. Their role in autonomously functioning thyroid carcinomas is not well established. We present a patient who had thyroidectomy for toxic multinodular goiter and a papillary carcinoma was demonstrated histopathologically. Genomic DNA was isolated from two solid areas in the hot nodule and peripheral leukocytes of the patient. After amplifying the related regions, TSHR and G(S)alpha genes were analyzed by single-strand conformation polymorphism (SSCP) analysis. The precise localization of the mutations was identified by automatic DNA sequence analysis. An activating mutation of the TSHR gene (Leu 512 Arg) was found in the autonomously functioning papillary carcinoma. It is believed that this mutation causes constitutive activation of the cyclic adenosine monophosphate (CAMP) signal transduction pathway and thereby causes thyrotoxicosis and a hot thyroid nodule in an autonomously functioning papillary carcinoma.
Keywords: TOXIC THYROID-NODULES; TSH RECEPTOR; ACTIVATING MUTATION; SOMATIC MUTATIONS; GEL-ELECTROPHORESIS; G(S)ALPHA; ADENOMAS; GENE; MANAGEMENT; THYROTOXICOSIS